Irregularity Cargo Management at Garuda Indonesia Semarang - Amy Hernyana Krishtantie; Marno Nugroho; Ari Pranaditya (Journal of Economics, Management, and Business, 2026)
Objective – This research aims to provide a practical contribution to air cargo operational management and serve as an academic reference for the development and study of air transportation management. Methods – This research utilizes literature review, document analysis, and comparison of handling reports with standard air transportation regulations. The findings are analyzed based on operational management concepts and aviation legal provisions. Results – The study of Garuda Indonesia Cargo Semarang indicates that the company has, in principle, fulfilled its legal responsibilities in accordance with applicable laws and regulations. This implementation is evident in the irregularity cargo handling mechanism, which includes a claims process and compensation for service users based on established internal procedures, and also refers to Law Number 1 of 2009 concerning Aviation, Minister of Transportation Regulation Number PM 77 of 2011 concerning Air Transport Responsibility for Domestic Shipments, and the 1999 Montreal Convention for International Shipments. Implications – The research results can serve as a basis for evaluating and improving air cargo operational management, particularly in preventing irregularity cargo. The research findings emphasize the importance of strengthening operational management, increasing reservation data accuracy, standardizing packaging, and improving coordination between airlines and cargo agents. Implementation of these recommendations is expected to reduce the risk of loss for both service users and airlines, increase legal certainty for service users, and strengthen trust in air cargo services. Originality - This research's originality lies in its analytical approach, which combines air cargo operational practices with national and international legal frameworks. This research not only assesses regulatory compliance but also links it to the operational management concept at Garuda Indonesia Cargo Semarang, focusing on cargo irregularity as the interface between operational risk and legal liability.